Manajemen Berbasis Madrasah sebagai Bentuk Desentralisasi Pendidikan - Nova Nurhakim (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2024)
Madrasah-based management is one of the efforts made so that madrasas can grow and develop independently. This writing aims to describe the application of madrasa-based management as a form of educational decentralization. This research method uses descriptive research using a literature study approach. The results of this research are: 1) Madrasah-based management is the result of decentralization; 2) One of the implementations of madrasa-based management is realized in the realm of madrasa financing; 3) Ciputat Development Madrasah is one of the institutions that implement madrasa-based management in the realm of good financing, one indicator is that they have 5 sources of financing (contributions from accepted students, tuition fees, BOS funds, new school year money, and sponsors). 4) Development madrasah invest some of the BOS funds they receive in accordance with the dimensions of restructuring the old pattern into a new pattern of madrasa-based management.